Speech Sound Disorder and Visual Biofeedback Intervention: A Preliminary Investigation of Treatment Intensity - Hitchcock, Elaine R.; Swartz, Michelle T.; Lopez, Melissa (Seminars in Speech and Language, 2019)
A growing body of research suggests that cases of speech sound errors that have not responded to previous intervention can sometimes be eliminated through speech therapy incorporating visual biofeedback. Aside from considerations related to the specific biofeedback type, acquisition and generalization of a motor plan may be linked to treatment intensity. Several researchers have raised the possibility that inadequate dosage levels may present a significant barrier to success. Thus, the current study aimed to assess the relationship between treatment intensity and treatment outcomes. Twenty-nine articles reporting the use of visual biofeedback intervention for speech sound disorder were identified and coded for treatment intensity using the cumulative intervention index and outcomes using mean level difference scores. Findings reveal small but significant relationships between measures of treatment intensity and efficacy, which should be interpreted with caution given the preliminary nature of this review. Further research in this area is necessary, as inconsistencies in reporting intensity and outcomes across studies underscore the need for more systematic terminology and reporting methods.
Keywords: residual speech errors; childhood apraxia of speech; treatment intensity; dose; visual biofeedback